تأثير المحاسبة الابداعية على جودة القوائم المالية )دراسة استطلاعية لعينة في المؤسسات الاقتصادية بالشرق جزائري( - خليل مباركي; أيمن رحال (My University, 2022)
Creative accounting is generally a set of methods available within accounting rules, namely, the exploitation of the elements of flexibility and choice in those rules and practiced by companies with the aim of improving the financial position and influencing the impression of users of financial statements. The study found that creative accounting is practiced to manipulate numbers and accounts in order to reach specific objectives as well as to mislead the users of financial statements, and therefore the auditor must detect errors and fraud and be smart to avoid falling into wrong administrative and financial practices and to detect cases of manipulation of reports, financial lists, cases of corruption and all immoral professional conduct, To achieve this study, we conducted a survey of the opinions of a sample of accountants in EL oued and found through the results of statistical tests a strong correlation between creative accounting and the quality of financial statements and a significant impact among the variables of the study and we found that creative accounting methods contribute to the unreliability of financial statements and influence those who use them .............................. تهدف هذه الدراسة الى أن المحاسبة الإبداعية بصفة عامة هي مجموعة من الأساليب المتاحة ضمن القواعد المحاسبية وهي استغلال عنصري المرونة والإختيار في تلك القواعد وتمارسها الشركات بهدف تحسين المركز المالي والتأثير على إنطباع مستخدمي القوائم المالية. و توصلت هذه الدراسة إلى أن المحاسبة الإبداعية تمارس للتلاعب بالأرقام والحسابات بغية الوصول إلى أهداف محددة وكذلك لتضليل مستخدمي القوائم المالية، وبالتالي وجب على مدقق الحسابات أن يكتشف الأخطاء والتدليس وأن يتحلى بالفطنة تجنبا للوقوع في الممارسات الإدارية والمالية الخاطئة والكشف عن حالات التلاعب في التقارير والقوائم المالية وحالات الفساد وكل التصرفات المهنية اللاأخلاقية، ولتحقيق هذه الدراسة قمنا بدراسة إستطلاعية لآراء عينة من المحاسبين بولاية الوادي وقد تبين من خلال نتائج الاختبارات الإحصائية وجود علاقة إرتباط قوية بين المحاسبة الإبداعية و القوائم المالية و وجود تأثير كبير بين متغيري الدراسة كما توصلنا إلى أن أساليب المحاسبة الإبداعية تساهم في عدم موثوقية القوائم المالية والتأثير على من يستخدمها.